PELATIHAN AKUAPONIK TANAMAN PAKCOY UNTUK PEMBERDAYAAN EKONOMI DI DESA CIKARAGEMAN - Silmi Hidayanti, Putri; Primasari, Winda; Rikmasari, Rima (An-Nizam, 2025)
This community service activity focuses on training PKK mothers in Cikarageman Village on processing healthy and nutritious food using pakcoy (Brassica rapa subsp. chinensis). Pakcoy is widely cultivated in the area and is rich in essential nutrients such as vitamins A, C, and K, as well as minerals like calcium and iron. Despite its nutritional value, its utilization as a primary food ingredient remains limited among local communities. This training aims to enhance participants' knowledge and skills in processing pakcoy into various food products, increasing both its household consumption and economic potential. The training employs a combination of theoretical lectures, demonstrations, and hands-on practice. Participants learn about the health benefits of pakcoy and how to transform it into diverse, appealing food products such as pakcoy juice and other nutritious meals, personal health benefits, this initiative has economic implications.